La interculturalidad en la enseñanza y aprendizaje de español como lengua extranjera: una propuesta didáctica - CARDOSO, Natália Moraes (2019)
The objective of this work is to understand the importance of making the learner of Spanish as a foreign language establish a relationship of awareness among their own culture and that belonging to the Spanish-speaking communities in order to relate to the immanent differences in the people, through intercultural dialogue. For this, we develop in this text reflections on the understanding of culture for teaching Spanish as a foreign language (E/LE); next, we try to expand the concept of communicative competence that is a key concept to language teaching; therefore, we reflected on the need to promote intercultural dialogue in the Spanish classroom and, finally, we proposed an intercultural-based didactic activity. The chosen approach for this work was of a qualitative nature, since the object that has been studied is not configured as something that can be quantified or measured, on the contrary, it is an interpretive and explanatory analysis since it seeks to understand how interculturality can add many advantages to the teaching and learning of E / LE. In the theoretical foundation of this work we talk with authors who deal with the teaching and learning of foreign languages such as Melero Abadía (2000); then, we went to authors who added the cultural aspect in their contributions as Miquel & Sanz (1992); and also, with special emphasis, authors who discuss the demand for an education based on interculturality, among them we mention Paraquett (2011); Tubino (1994) among other authors. At the end of this work we conclude that even in a context of regression in the teaching and learning of Spanish in Brazil, we consider too much its importance for an intercultural formation that goes beyond the walls of the school, for a formation of belonging of Brazilians as Latinos, because geographically we are so close, but still so far in aspects of (re) knowledge of singularities that are part of the Hispanic world, which in addition to speaking Spanish as an aspect of union, has specific features that belong to each culture.